Decoding bronchopulmonary dysplasia in premature infants through an epigenetic lens - Seyed Alireza Dastgheib; Reza Bahrami; Mohammad Golshan-Tafti; Mahsa Danaei; Sepideh Azizi; Amirhossein Shahbazi; Maryam Yeganegi; Amirmasoud Shiri; Ali Masoudi; Hossein Neamatzadeh (Frontiers in Medicine)
This review provides a comprehensive overview of the evolving insights into the epigenetic mechanisms associated with bronchopulmonary dysplasia (BPD). It specifically highlights the roles of DNA methylation, histone modifications, and RNA regulation in the development of BPD in premature infants. BPD results from complex interactions among genetic factors, environmental exposures, and neonatal stressors. Key findings suggest that intrauterine hypoxia, hyperoxia, and nutrition can lead to epigenetic alterations, affecting gene expression and methylation, which may serve as biomarkers for early BPD detection. RUNX3 is identified as a critical transcription factor influencing lung development and inflammation, while changes in DNA methylation and histone dynamics in cord blood are linked to immune dysregulation associated with BPD. The role of m6A RNA methylation regulators from the IGF2BP family affects mRNA stability and gene expression relevant to BPD. Additionally, specific histones and microRNAs, particularly from the miR-17∼92 cluster, are implicated in pulmonary development and vascular regulation. Long non-coding RNAs (lncRNAs), such as MALAT1, also play a role in gene regulation via competitive endogenous RNA networks, indicating their potential as biomarkers and therapeutic targets. The interplay of these epigenetic mechanisms underscores the need for further research to develop targeted interventions aimed at reducing BPD severity and enhancing health outcomes for at-risk neonates.